The Influence of Corporate Governance Mechanism and Age of Company To Time Compliance of Financial Reporting (Empirical Study on Mining Sector Companies That Listed on Indonesia Stock Exchange in 2010-2012). - Randi Hermawan Bulo; M. Yasser Arafat; Ratna Anggraini (Jurnal Ilmiah Wahana Akuntansi, 2016)
The objective of study examines the influence of mechanism corporate governance consist of managerial ownership and institutional ownership, and then age of company on timeliness of corporate financial reporting. This research represents the empirical test which used purposive sampling techniques in data collection. Data were collected using a secondary data of 28 from mining company listed in Indonesian Stock Exchange 2010-2012. Data analysis uses multiple regression with the program SPSS 16.00 version for windows. Results of hypothesis examination indicate there is influence between institutional ownership and age of company on Timeliness of Corporate Financial Reporting, and there is no influence between Managerial ownership on Timeliness of Corporate Financial Reporting. Keywords: Timeliness, Managerial Ownership, Institutional Ownership, Age of Company